Design and preparation method of aluminum oxide ceramic insulating part for vacuum
By adopting macro-metastructure integrated design and photocuring ceramic 3D printing technology in ceramic insulated components, the problem of flashover along the surface in high vacuum environments is solved, and the electrical resistance strength and equipment stability are significantly improved.
Patent Information
- Application Number
- CN202311693980.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-12-08
AI Technical Summary
Existing ceramic insulated components are prone to flashover along the surface in high vacuum environments, which reduces the electrical resistance and limits the improvement of device voltage levels and the development of miniaturization and compactness.
Using the design method of vacuum alumina ceramic insulated components, the macroscopic structure of ceramic insulated components is optimized to homogenize the electric field distribution, and a complex mesostructure is designed on the surface to suppress secondary electron multiplication. At the same time, the 3D printing technology of photocuring ceramics is used for forming, avoiding the steps of mechanical processing and mold opening.
It effectively improves the electrical resistance of ceramic insulated components along the edge, enhances the stability of the equipment, shortens the product development cycle, improves production efficiency, and significantly increases the service life of the insulating equipment.
Smart Images

Figure CN119638378A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of design and preparation of ceramic insulating components, and in particular to a design and preparation method of an alumina ceramic insulating component for vacuum. Background Art
[0002] Ceramic insulating components play multiple roles in vacuum devices / equipment such as electron beam lithography machines, pulse power equipment, high-energy electron guns, and CT tubes, including electrical insulation, mechanical support, and air pressure isolation, and have become one of the indispensable core components in the device. However, in a high vacuum environment, since ceramic insulating components are in a high voltage and strong electric field working environment, the composite interface formed by vacuum and solid insulation is prone to surface discharge breakdown, also known as surface flashover. The existence of surface flashover greatly reduces the withstand voltage strength of the entire insulation system, limiting the improvement of the device voltage level and the urgent development of miniaturization and compactness.
[0003] In order to improve the surface dielectric strength of vacuum ceramic insulation systems, the existing methods can be summarized into three technical routes. The first method is to reduce the initial electrons generated from the cathode triple junction at the initial stage of surface flashover. The second method is to suppress the secondary electron multiplication process on the surface of ceramic insulation at the development stage of flashover. The third method is to suppress the surface gas desorption at the final flashover breakdown stage and increase the voltage threshold for forming a penetrating discharge in the surface desorbed gas layer. The specific principles of the existing technology in the three stages of flashover will be introduced in detail below.
[0004] Initial stage: In order to reduce the maximum electric field intensity at the triple junction, the surface electric field distribution is improved by optimizing the geometric structure of the ceramic insulating component / metal electrode; by designing graded insulation, the relative dielectric constant or conductivity of the insulating matrix is increased, and a gradient distribution structure is constructed to improve the surface electric field distribution.
[0005] Development stage: In order to suppress the multiplication of secondary electrons, the secondary electron emission coefficient of the surface of ceramic insulation can be reduced by surface treatment and other means; the development of electron avalanche can be hindered by forming an ordered or disordered microgroove structure on the ceramic surface;
[0006] Breakdown stage: In order to suppress the probability of outgassing on the material surface, voltage aging or baking are used to remove or block the gas molecules adsorbed on the surface.
[0007] Based on the above method and principle of increasing the flashover voltage, for existing vacuum ceramic insulation components, the specific implementation process usually covers the following two aspects:
[0008] 1) Preparation of ceramic insulation components
[0009] a. Material selection: Vacuum ceramic insulation components usually use ceramic materials such as high-purity alumina (Al2O3) or silicon nitride (Si3N4) as the base material. These materials have excellent insulation properties, high temperature stability, and resistance to chemical corrosion.
[0010] b. Forming process: The traditional forming method of ceramic insulation is to use molds, cutting, grinding and other methods to remove excess materials based on raw materials to obtain parts. Specific forming processes include injection molding, pressing molding and grouting molding.
[0011] c. Sintering process: Place the formed ceramic parts into a high-temperature furnace and heat them at a certain temperature to allow the ceramic particles to combine and form a dense structure.
[0012] 2) Process for improving the electrical strength along the surface of ceramic insulation components
[0013] a. Initial stage: improving electric field distribution through geometric structure optimization. Usually, before the preparation of ceramic insulating components, a better electrode or ceramic insulating component geometric profile is designed through an optimization algorithm; after the preparation of the ceramic insulating components, a shielding electrode can be set to suppress the electric field strength at the three junctions; on the other hand, an ABA-type sandwich structure can also be used to bond and combine the prepared ceramic insulating components with different dielectric constants into a new ceramic insulating component structure, and the electric field strength at the three junctions can be suppressed through graded insulation.
[0014] b. Development stage: After the preparation of ceramic insulating components, post-treatment methods are usually used to suppress secondary electron multiplication. Specific implementation methods include: surface laser grooving, surface coating, surface ion implantation, surface thermal spray coating, surface polishing, surface direct fluorination and surface plasma treatment and other material surface treatment methods.
[0015] c. Breakdown stage: After the preparation of the ceramic insulating components is completed, the gas molecules adsorbed on the surface are removed or blocked through continuous surface voltage aging treatment or thermal baking.
[0016] 1) The existing ceramic insulation component preparation method is based on the mold forming process, which limits the complexity and flexibility of the component shape and may not meet the needs of components with special shapes. In addition, the material removal process in the traditional method may lead to material waste, and the mold opening process will increase manufacturing time and economic costs.
[0017] 2) The surface treatment methods currently used have a certain degree of randomness. Factors such as the treatment process, treatment time and type of base material will increase the uncertainty of the obtained surface structure, which in turn affects the repeatability and timeliness of the effect of improving the surface electrical strength. Furthermore, although there are many existing surface treatment methods, the preparation efficiency is low, such as surface laser grooving or mechanical grooving, and the microstructure needs to be prepared one by one by moving the workpiece or grooving equipment. It may also cause cracks and affect the life of ceramic insulating components. Surface coating treatment is prone to falling off, which reduces the service life of the equipment and is difficult to maintain the modification effect for a long time.
[0018] 3) At present, the means of increasing the surface flashover voltage of ceramic insulation is only optimized for a certain stage of flashover, which cannot provide sufficient flexibility and reliability to ensure the deep suppression of surface flashover. Therefore, it is necessary to comprehensively consider the optimization measures at different stages and realize the system integration of flashover suppression methods at each stage. To this end, a design and preparation method of a vacuum alumina ceramic insulation component is proposed. Summary of the invention
[0019] The technical problem to be solved by the present invention is: how to improve the overall surface electrical strength of ceramic insulating components. A design method for alumina ceramic insulating components for vacuum use is provided. Starting from both the initiation and development stages of surface flashover, an integrated macro-micro structure design method for ceramic insulating components is proposed, which can achieve deep suppression of surface flashover.
[0020] The present invention solves the above technical problems through the following technical solutions, and the present invention comprises the following steps:
[0021] S1: Optimizing the macrostructure to control the electric field distribution along the surface
[0022] With the optimization goal of homogenizing the electric field along the surface of the ceramic insulating component and reducing the electric field intensity at the cathode triple junction, the finite element method is used to discretize the ceramic insulating component region to obtain multiple grids. The dielectric constant in each grid varies in the range from the substrate dielectric constant to the vacuum dielectric constant. Through the variable density topology optimization algorithm, and considering the mechanical performance requirements and the limitations of the algorithm parameter value range, the optimal spatial distribution of the dielectric constant inside the supporting ceramic insulating component is found, and then the macro structure is obtained;
[0023] S2: Microstructure optimization and control of secondary electron multiplication
[0024] Microstructures of different sizes are randomly generated on the surface of the macrostructure. Subsequently, particle simulation and Monte Carlo collision method are used to carry out surface discharge simulation research. The particle simulation method is used to track the motion state of particles, and the Monte Carlo collision method is used to deal with the collision process between particles. By reconstructing the secondary electron multiplication process, the surface structure size parameters of microstructures with low secondary electron yield are obtained, and then the mesostructure is obtained.
[0025] Furthermore, in the step S1, the design optimization variable is the relative dielectric constant in each grid after the dielectric constant optimization region Ω1 is discretized, which is expressed as follows:
[0026] ε(r,z),(r,z)∈Ω1
[0027] Among them, r and z are the horizontal and vertical coordinates in the two-dimensional axisymmetric coordinate system, and the dielectric constant of each point after discretization is recorded as ε(r,z);
[0028] After the optimization variables are determined, the mathematical expression of the optimization target f is obtained as follows:
[0029]
[0030] Among them, f1 is the electric field optimization term, f2 is the gradient penalty term, the weight coefficient q is used to control the proportion of the gradient penalty term in the total optimization target, Ω1 is the dielectric constant optimization area, Ω2 is the surface electric field optimization area; Ω3 is the local electric field optimization area at CTJ, C ref1 and C ref2 are the normalized parameters of the optimized components in the electric field integral term, A, h mesh and ρ are the area of the dielectric constant optimization region Ω1, the maximum size of the mesh, and the material density in the mesh, respectively. E is the electric field intensity in the surface electric field optimization region Ω2, and E mean is the average electric field strength along the surface.
[0031] Furthermore, in step S1, the relationship between the material density ρ in the grid and the relative dielectric constant is as follows:
[0032]
[0033] Among them, ε ri , ε max and ε min are the dielectric constant, the upper limit of dielectric constant change and the lower limit of dielectric constant in the i-th grid, m is the shape control coefficient of density function, ρ i is the material density in the i-th grid.
[0034] Furthermore, in step S1, when the finite element analysis is performed using the variable density topology optimization algorithm, the stress distribution of each grid under a given mechanical load is calculated at the same time, and the relationship between stress and strain is expressed by Hooke's law:
[0035] σ=M*ε
[0036] Where σ is stress, M is the elastic modulus of the material, and ε is strain;
[0037] The strain of each grid is calculated by finite element method to obtain the maximum stress S of the entire ceramic insulation component. max and the maximum deformation D max ;
[0038] It is stipulated that the maximum deformation of ceramic insulation components under a given mechanical load shall not exceed the allowable value D f ,Right now:
[0039] D max ≤D f
[0040] That is, the constraints on the mechanical strength of the ceramic insulating component are obtained.
[0041] Furthermore, in step S1, when performing finite element analysis using the variable density topology optimization algorithm, the following constraints are also included:
[0042] 1≤m≤10,0<ρ i <1,0≤q≤10;
[0043] The final optimization problem is:
[0044] Design variables: ε(r,z),(r,z)∈Ω1
[0045] Optimization goal:
[0046] Constraints:
[0047] 0<m<10,0<ρ i <1,0≤q≤10
[0048] D max ≤D f
[0049] Through multi-physics finite element simulation of electric field and solid mechanics field, the optimization parameters m, q and D are adjusted. max , and obtain the optimal spatial distribution of the dielectric constant inside the supporting ceramic insulating component.
[0050] Furthermore, after determining the optimization objectives and constraints, finite element simulation analysis software is used to establish the electric field and force field simulation model of the ceramic insulating component, and the global moving asymptote optimization algorithm is used to solve the optimization problem, obtain the optimized material density distribution of the ceramic insulating component, and obtain the macro structure.
[0051] Furthermore, in step S2, the specific surface discharge simulation process is as follows:
[0052] S21: Set the minimum forming size S of the microstructure min, dividing the macrostructure surface into N grid matrix units, using different types of lattice lattice structures, and determining the relationship between the minimum lattice lattice structure size parameters;
[0053] S22: The obtained structures of different sizes are simulated by particle simulation and Monte Carlo collision method to simulate the electric field distribution and the motion trajectory of charged particles during the secondary electron multiplication process, and the optimized lattice structure size parameters are obtained to improve the vacuum surface electrical strength of the material.
[0054] Furthermore, in the step S21, the minimum lattice lattice structure size parameters include: the length l0 and width d0 of the lattice lattice, the height h0 of the lattice lattice, and the diameter z0 of the lattice lattice column. The relationship between the size parameters is as follows:
[0055]
[0056] Furthermore, in step S22, the specific process of performing simulation by particle simulation and Monte Carlo collision method is as follows:
[0057] S221: Particle Data Processing
[0058] At a given incident angle θ and bombardment energy E i Under this condition, the total secondary electron emission coefficient δ is determined as follows:
[0059]
[0060]
[0061]
[0062] Among them, δ max is the maximum secondary electron emission coefficient corresponding to the secondary electron emission curve at vertical incidence, E max is the corresponding incident electron energy; k s is the roughness coefficient; E min is the minimum electron energy that triggers secondary electron emission;
[0063] According to the emission coefficients of the three types of electrons obtained above, the three types of electrons are: primary electrons scattered elastically; primary electrons scattered inelastically; true secondary electrons;
[0064] S222: Electromagnetic Field Data Processing
[0065] In the electrostatic model, the Poisson equation is solved by the explicit FDTD method to obtain the electrostatic potential, and the electrostatic field is obtained by solving the potential gradient equation. In the electromagnetic model, in order to circumvent the time step restriction of the CFL condition, the Maxwell equations are solved by the implicit FDTD method to obtain the RF electromagnetic field distribution, and the electrostatic field is solved in the same way as in the electrostatic model.
[0066] S223: Particle data and grid data interaction
[0067] The interaction between particles and grid data includes two processes: from particle data to grid data and from grid data to particle data. In the process of interaction from particle data to grid data, the charge density and current density on the grid are calculated based on the parameters such as the position and charge of the particle. In the process of interaction from grid data to particle data, the electromagnetic field of the grid is interpolated to the particle, thereby calculating the force on the particle.
[0068] S224: Particle Collision Processing
[0069] The Coulomb collision process between charged particles is treated by the Monte Carlo collision method.
[0070] The present invention also provides a method for preparing an alumina ceramic insulating component for vacuum use. Based on the macroscopic structure and microscopic structure obtained by the above-mentioned design method, the ceramic insulating component is formed by using a photocuring ceramic 3D printing technology, which includes the following steps:
[0071] S3: Stereolithography 3D Printing
[0072] Alumina powder with a mass fraction of 70-85%, photocurable resin with a mass fraction of 5-14%, acrylate monomer with a mass fraction of 5-18%, UV photoinitiator with a mass fraction of 1-5%, and other additives with a mass fraction of 1-3% are dispersed and stirred using a vacuum planetary gravity mixer at a constant temperature of 40-50° C. The stirring speed is 1000-2000 rpm, and after stirring for 5-10 minutes, a mixed slurry with uniform dispersion and no bubble defects is obtained; the prepared mixed slurry is placed in a 3D printer material tank, and 3D printing is performed by a photocuring 3D printer to obtain an alumina ceramic component embryo;
[0073] S4: Ceramic degreasing
[0074] First, the temperature was raised from room temperature to 600°C at a heating rate of 1°C / min in a vacuum environment, and the temperature was kept at 200, 250 and 300°C for 90 minutes respectively, and at 600°C for 150 minutes; after the temperature dropped to room temperature, air was introduced into the tubular furnace, and the temperature was raised from room temperature to 600°C at a heating rate of 1°C / min, and then kept for 120 minutes and cooled with the furnace;
[0075] S5: Ceramic sintering
[0076] The sintering is completed in a high-temperature box furnace at 1750°C. During sintering, the temperature is first raised to 1400°C at a rate of 10°C / min, kept warm for 120 minutes, then raised to 1600°C at a rate of 5°C / min, and kept warm for 120 minutes; finally, the temperature is slowly raised to 1700°C at a rate of 2°C / min, and kept warm for 60 minutes to fully densify the ceramic body; finally, the temperature is naturally lowered to room temperature, and the sintered dense alumina component is taken out, that is, the alumina ceramic insulating component is obtained.
[0077] Compared with the prior art, the present invention has the following advantages: the design and preparation method of the vacuum alumina ceramic insulation component integrates the two stages of vacuum surface flashover initiation and development for integrated optimization design and model construction, effectively reducing the generation of initial electrons and inhibiting the multiplication of secondary electrons, which not only greatly improves the electrical strength of the entire insulation system, but also significantly improves the stability of the equipment; using the ceramic 3D printing light curing layer-by-layer printing method, without mechanical processing or mold opening, only a 3D printer with ultraviolet digital forming technology is needed to directly generate ceramic components with complex shapes and delicate graphics from computer graphics data, which greatly shortens the product development cycle, improves production efficiency, and reduces production costs; the surface microstructure is formed by printing and forming, avoiding the crack problem that may occur in the post-processing process. This significantly increases the service life of the insulation equipment and improves the reliability of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Figure 1 It is a schematic flow chart of a design and preparation method of an alumina ceramic insulating component for vacuum use in the first embodiment of the present invention;
[0079] FIG2( a ) is a schematic diagram of the minimum lattice lattice structure used in the microstructure optimization process in Example 1 of the present invention;
[0080] FIG2( b ) is a schematic diagram of a structure formed by arranging and combining multiple minimum lattice lattice structures in FIG2( a );
[0081] Figure 3 Schematic diagram of the initial structure of the ceramic insulating component of the strong parallel electric field in the second embodiment of the present invention;
[0082] Figure 4 Schematic diagram of the optimized structure of the ceramic insulating component of the strong parallel electric field in the second embodiment of the present invention;
[0083] Figure 5 Schematic diagram of the initial structure of the ceramic insulating component with a strong vertical electric field in the third embodiment of the present invention;
[0084] Figure 6 Schematic diagram of the optimized structure of the ceramic insulating component with a strong vertical electric field in the third embodiment of the present invention;
[0085] Figure 7 is a schematic diagram of the initial structure of the ceramic insulating component of the hybrid electric field in the fourth embodiment of the present invention;
[0086] Figure 8 It is a schematic diagram of the optimized structure of the ceramic insulating component of the hybrid electric field in the fourth embodiment of the present invention. DETAILED DESCRIPTION
[0087] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0088] Embodiment 1
[0089] This embodiment provides a technical solution: a design method for a vacuum alumina ceramic insulation component, which mainly includes the following main contents:
[0090] Initial stage: By controlling the macroscopic material density distribution of ceramic insulation, a macroscopic functional gradient structure is formed to actively homogenize the electric field distribution, reduce the field intensity concentration phenomenon at the cathode triple junction (CTJ), and thus increase the flashover voltage.
[0091] Development stage: Starting from the perspective of suppressing the multiplication of secondary electrons, the controllable design of the surface secondary electron yield and the manufacturing constraints of the complex structure are comprehensively considered to design a complex and ordered mesostructure on the ceramic surface, that is, a mesocomplex microstructure.
[0092] This embodiment provides a technical solution: a method for preparing a vacuum alumina ceramic insulating component, which mainly includes the following contents:
[0093] In terms of preparation method, the present invention adopts light-curing ceramic 3D printing technology, and through layer-by-layer accumulation, the macroscopic functional gradient structure designed in advance in the design method of vacuum alumina ceramic insulating components and the microscopic complex microstructure are integrated and directly printed into a solid component. No complicated mold preparation process is required, which improves the complexity and flexibility of the component shape and avoids material waste.
[0094] Specifically, the design method and preparation method of the above-mentioned vacuum alumina ceramic insulation component are further explained below.
[0095] like Figure 1 As shown, a design method of a vacuum alumina ceramic insulation component in this embodiment includes the following two aspects:
[0096] 1. Macrostructure optimization and control of surface electric field distribution
[0097] Firstly, to address the problems of abnormally high electric field at CTJ and uneven distribution of the overall electric field along the surface, a gradient distribution of the dielectric constant of ceramic insulation is constructed through topology optimization numerical simulation, and dielectric functional gradient insulation is constructed to achieve the goal of reducing the field strength at the cathode triple junction and homogenizing the electric field along the surface, thereby increasing the flashover voltage.
[0098] Specifically, the ceramic insulating component is discretized with the optimization goal of homogenizing the electric field along the surface of the ceramic insulating component and reducing the electric field intensity at the CTJ. The dielectric constant in each tiny unit varies in the range of the substrate dielectric constant (here the dielectric constant of alumina ceramic at the power frequency is 11) to the vacuum dielectric constant (the value is 1). The optimal spatial distribution of the dielectric constant (i.e., material density) inside the supporting ceramic insulating component is found through the variable density topology optimization algorithm.
[0099] The design variable is the relative dielectric constant in each tiny unit after the dielectric constant optimization region Ω1 is discretized, which can be specifically expressed as:
[0100] ε(r,z),(r,z)∈Ω1 (1)
[0101] Among them, r and z are the horizontal and vertical coordinates in the two-dimensional axisymmetric coordinate system, respectively. The dielectric constant of each point after discretization is recorded as ε(r,z). After the optimization variables are determined, the optimization target f can be mathematically expressed as:
[0102]
[0103] Among them, f1 is the electric field optimization term, f2 is the gradient penalty term, the weight coefficient q is used to control the proportion of the gradient penalty term in the total optimization target, Ω1 is the dielectric constant optimization area, Ω2 is the surface electric field optimization area; Ω3 is the local electric field optimization area at CTJ, C ref1 and C ref2 are the normalized parameters of the optimized components in the electric field integral term, A, h mesh and ρ are the area of the dielectric constant optimization region Ω1, the maximum size of the mesh, and the material density in the mesh, respectively. E is the electric field intensity in the surface electric field optimization region Ω2, and E mean is the average electric field strength along the surface.
[0104] The relationship between the material density ρ in the grid and the relative dielectric constant is as follows:
[0105]
[0106] Among them, ε ri , ε max and ε minare the dielectric constant in the ith grid, the upper limit of the dielectric constant change (the dielectric constant of the alumina ceramic matrix, which is 11), and the lower limit of the dielectric constant (the dielectric constant of the vacuum, which is 1), respectively. m is the shape control coefficient of the density function, ρ i is the material density in the i-th grid.
[0107] In terms of constraints, while optimizing the electric field distribution by regulating the material distribution, the mechanical support strength of the ceramic insulating components must also be considered to meet the needs of actual engineering applications. Ceramic insulating components will generate internal reaction forces when subjected to force. This force is called stress. The magnitude and direction of the stress will affect its deformation and mechanical properties. When the stress on the ceramic insulating components exceeds their strength limit, it will cause the ceramic insulating components to crack and break. In the topology optimization finite element analysis, the structure of the ceramic insulating components has been discretized into a triangular mesh. Each finite element (mesh) has a set of nodes and material properties. According to the actual working conditions, appropriate boundary conditions and loading conditions are applied to these nodes, and the stress distribution of each finite element is calculated. The relationship between stress and strain can be expressed by Hooke's law:
[0108] σ=M*ε (4)
[0109] Where σ is stress, M is the elastic modulus of the material, and ε is strain.
[0110] By calculating the strain of each grid, the maximum stress S of the entire ceramic insulation component is finally obtained. max and the maximum deformation D max . Due to S max It has a strong grid dependence, and the calculation results under different grid densities vary greatly. In order to reflect the constraints of mechanical properties, it is again stipulated that the maximum deformation of ceramic insulation components under a given mechanical load shall not exceed the allowable value D f ,Right now:
[0111] D max ≤D f (5)
[0112] In addition to the mechanical strength constraint, other constraints determined during topology optimization based on the finite element method include:
[0113] 1≤m≤10,0<ρ i <1,0≤q≤10 (6)
[0114] Wherein, m is the shape control coefficient of the density function, which is usually an integer.
[0115] In summary, the final optimization problem can be summarized as:
[0116] Design variables: ε(r,z),(r,z)∈Ω1
[0117] Optimization goal:
[0118] Constraints:
[0119] 0<m<10,0<ρ i <1,0≤q≤10
[0120] D max ≤D f
[0121] Based on the above formula, the optimization parameters m, q and D are adjusted through multi-physics finite element simulation of electric field and solid mechanics field. max , find out the spatial distribution of dielectric constant that is suitable for manufacturing and has good optimization effect, that is, obtain the spatial distribution of dielectric constant (that is, material density) optimized inside the supporting ceramic insulating component.
[0122] Specifically, finite element simulation analysis software is used to establish the electric field and force field simulation models of ceramic insulation components, and the global moving asymptote optimization algorithm is used to gradually approach the optimal solution by continuously adjusting the search path and step size. The steps are as follows:
[0123] 1) Dielectric constant initialization: select material density ρ i Initial solution, and set the search step size and control parameters m, q, D max The specific value of
[0124] 2) Moving asymptote operation: According to the current parameter settings, the force field and electric field distribution are obtained through finite element calculation, and the moving operation is performed according to the step size and search direction to calculate and generate a new solution;
[0125] 3) Judgment criteria: If the absolute value error between the new solution and the last solution is less than 10 -4 Or the maximum number of iterations is reached. Then the optimal solution is returned; if the stopping criteria are not met, return to step 2) to perform the moving asymptote operation;
[0126] 4) Finally, the optimization problem in equation (7) is solved to obtain the optimized material density distribution of the ceramic insulation component to meet the requirements of electrical and mechanical strength.
[0127] 2. Microstructure optimization and control of secondary electron multiplication
[0128] After clarifying the optimized macroscopic structure, the secondary electron multiplication process on the insulating surface is taken into consideration to regulate the surface structure of ceramic insulating components at the microscopic scale, thereby deeply improving the surface electrical strength of ceramic insulating components.
[0129] Specifically, microstructures of different sizes are first randomly generated on the surface of the macrostructure. Then, particle simulation and Monte Carlo collision (PIC and MCC) techniques are used to carry out detailed surface discharge simulation research. The PIC method is used to track the motion state of particles, and the MCC method is used to deal with the collision process between particles. By reconstructing the secondary electron multiplication process, a microstructure surface with low secondary electron yield (SEY) is obtained.
[0130] The specific simulation process is as follows:
[0131] Under the requirement of minimum printing feature accuracy of 3D printing platform, the minimum forming size S of the microstructure is set min The surface of the macro structure is divided into N grid matrix units, and the lattice lattice structure shown in Figure 2 (a) is adopted. The lattice lattice structure in Figure 2 (a) is the minimum lattice lattice structure used in the micro structure optimization process, which is attached to the surface of the ceramic insulating component after the macro structure optimization. The minimum lattice unit size variables include: the length l0 and width d0 of the lattice lattice (determining the plane size of the surface groove), the height h0 of the lattice lattice (determining the depth of the surface groove), and the diameter z0 of the lattice lattice column. It should be pointed out that the following relationship is satisfied between the parameters:
[0132]
[0133] The obtained structures of different sizes are simulated by PIC and MCC methods. The PIC and MCC calculation process mainly includes the following four parts: particle data processing, electromagnetic field data processing, particle and electromagnetic field data interaction, and particle collision processing, as follows:
[0134] Particle data processing: Electrons incident from the surface of a material will be scattered by atoms (and electrons) in the material. The incident electrons will undergo a complex physical process during the scattering process, which may cause secondary electron emission. i Under this condition, the total secondary electron emission coefficient δ is as follows:
[0135]
[0136] Among them, δ max is the maximum SEY value (secondary electron emission coefficient value) corresponding to the secondary electron emission curve at vertical incidence, E max is the corresponding incident electron energy; k s is the roughness coefficient; E minis the minimum electron energy that triggers secondary electron emission. The current secondary electron phenomenological model believes that the total secondary electrons emitted from the material surface mainly include three parts: elastically scattered primary electrons; inelastically scattered primary electrons; true secondary electrons. From equation (9), the emission coefficients of the three types of electrons can be obtained.
[0137] Electromagnetic field data processing: In the electrostatic model, the Poisson equation is solved by the explicit FDTD method to obtain the electrostatic potential, and the electrostatic field is obtained by solving the potential gradient equation. In the electromagnetic model, in order to circumvent the restrictions of the CFL condition on the time step, the Maxwell equations are solved by the implicit FDTD method to obtain the RF electromagnetic field distribution, and the electrostatic field is solved using the same method as the electrostatic model.
[0138] Interaction between particle data and grid data: The interaction between particles and grid data includes two processes: from particle data to grid data and from grid data to particle data. The former mainly calculates the charge density and current density on the grid based on parameters such as the position and charge of the particle. The charge density is calculated using the area-based ZR bilinear interpolation method, and the current density is calculated using the charge conservation distribution scheme based on motion trajectory decomposition. From grid data to particle data, the electromagnetic field of the grid is interpolated onto the particle to calculate the force on the particle.
[0139] Particle collision processing: In a vacuum, the effect of Coulomb collisions is more significant. In order to more accurately describe the collision behavior of particles, the MCC method will be used to process the Coulomb collision process between charged particles. Specifically, the processing algorithm for Coulomb collisions between particles of unequal weights proposed by Higginson et al. is used.
[0140] After the microstructure is simulated through the PIC / MCC algorithm, the electric field distribution and the motion trajectory of charged particles during the secondary electron multiplication process can be simulated with high accuracy, and the optimized lattice size parameters can be obtained, thereby effectively improving the vacuum surface electrical strength of the material.
[0141] A method for preparing a vacuum alumina ceramic insulating component in this embodiment includes the following two aspects:
[0142] 1) Light-curing 3D printing
[0143] After the design is completed, ceramic components with complex shapes and exquisite graphics are generated directly from computer graphics data, and the forming of ceramic insulation components is realized through ceramic 3D printing technology. The specific steps are as follows:
[0144] a. According to the mass fraction, 70-85% of alumina powder, 5-14% of photocurable resin, 5-18% of acrylate monomer, 1-5% of UV photoinitiator, and 1-3% of other additives (including defoamer, ultraviolet absorber, etc.) are dispersed and stirred using a vacuum planetary gravity mixer at a constant temperature of 40-50°C at a stirring speed of 1000-2000 rpm. After stirring for 5-10 minutes, a mixed slurry with uniform dispersion and no bubble defects is obtained;
[0145] b. Put the prepared mixed slurry into the trough of a 3D printer, and perform 3D printing by a photocuring 3D printer to obtain an alumina ceramic component embryo.
[0146] In the photocuring 3D printing process, the equipment applies 405nm ultraviolet light to a resin layer of a certain thickness, and performs 3D printing layer by layer. When ultraviolet light is irradiated into the slurry, on the one hand, the photosensitive resin absorbs ultraviolet light to undergo a photocuring reaction, and on the other hand, the alumina ceramic particles reflect ultraviolet light, weakening the radiation effect of the light in the slurry, thereby reducing the thickness of the cured layer. According to the Beer-Lambert law, the curing depth of the photosensitive resin satisfies:
[0147] C d =D p ln(E r / E c ) (10)
[0148] Among them, C d At the exposure energy E r The layer thickness that can be formed by light curing, E r is the ultraviolet light energy, E c D is the critical exposure, that is, the energy required when the resin just starts to cure. Its value mainly depends on the resin formula, resin oxygen content, etc. p It is a photosensitive parameter, which is a function of the properties of ceramic particles and the optical properties of photocurable resin materials. It ensures that the green body has sufficient interlayer bonding force during the printing process, so that the printing process proceeds smoothly and the green body is formed completely.
[0149] 2) Ceramic degreasing and sintering
[0150] Degreasing is a crucial part of the entire sintering process. Different degreasing processes have a significant impact on whether the ceramic body is fully degreased. When degreasing directly in the air, the pyrolysis rate of organic matter is higher, but the gas cannot escape completely, resulting in defects such as pores. When degreasing in a vacuum, the pyrolysis rate of organic matter is slow, but due to the scarcity of oxygen, the carbon produced by the pyrolysis of organic matter cannot be removed by reaction. Therefore, combining the advantages of sufficient pyrolysis in air degreasing with the advantages of gas escape in vacuum degreasing will help to completely remove organic matter in the ceramic body and reduce defects such as pores and cracks. In order to remove impurities other than alumina to the greatest extent, a high-temperature sintering furnace is used to degrease the ceramic body. The specific process is as follows:
[0151] a. First, raise the temperature from room temperature to 600°C at a heating rate of 1°C / min in a vacuum environment. During this period, keep the temperature at 200, 250 and 300°C for 90 minutes respectively, and keep it at 600°C for 150 minutes.
[0152] b. After the temperature drops to room temperature, introduce air into the tube furnace. Raise the temperature from room temperature to 600°C at a rate of 1°C / min, keep warm for 120 minutes, and then cool with the furnace.
[0153] c. After debinding, sintering is completed in a high-temperature box furnace at 1750°C. During sintering, the temperature is first raised to 1400°C at a rate of 10°C / min, kept at this temperature for 120 minutes, then raised to 1600°C at a rate of 5°C / min, and kept at this temperature for another 120 minutes.
[0154] d. Finally, the temperature was slowly raised to 1700°C at a rate of 2°C / min and kept at this temperature for 60 minutes to fully densify the ceramic body. Finally, the temperature was naturally lowered to room temperature and the sintered dense alumina component was taken out.
[0155] Embodiment 2
[0156] Ceramic insulating components with strong parallel electric fields, the initial structure is as follows Figure 3 As shown, it is commonly used in high-energy electron guns, electron beam lithography machines, and pulse power equipment to introduce high-voltage sources into vacuum chambers. After the design and preparation method in Example 1 optimizes the macroscopic topological structure and the microscopic lattice structure, the optimized ceramic insulating component structure is as follows Figure 4 shown.
[0157] Embodiment 3
[0158] Ceramic insulating components with strong vertical electric fields, the initial structure is as follows Figure 5As shown, it is commonly used in vacuum devices such as low-light night vision devices. The ceramic insulating component plays the role of bearing high voltage and vacuum sealing. After the design and preparation method in Example 1 optimizes the macroscopic topological structure and the microscopic lattice structure, the optimized ceramic insulating component structure is as shown in FIG. Figure 6 shown.
[0159] Embodiment 4
[0160] Ceramic insulating components of hybrid electric field, initial structure such as Figure 7 As shown, it plays the role of supporting metal guide rods and isolating potential in large vacuum equipment such as common pulse power equipment. After the design and preparation method in Example 1 optimizes the macroscopic topological structure and the microscopic lattice structure, the optimized ceramic insulating component structure is as shown in FIG. Figure 8 shown.
[0161] In summary, the design and preparation method of the vacuum alumina ceramic insulation component of the above embodiment integrates the two stages of vacuum surface flashover initiation and development for integrated optimization design and model construction, effectively reducing the generation of initial electrons and inhibiting the multiplication of secondary electrons, which not only greatly improves the electrical strength of the entire insulation system, but also significantly improves the stability of the equipment; using the ceramic 3D printing light curing layer-by-layer printing method, without mechanical processing or mold opening, only a 3D printer with ultraviolet digital forming technology is needed to directly generate ceramic components with complex shapes and delicate graphics from computer graphics data, which greatly shortens the product development cycle, improves production efficiency, and reduces production costs; the surface microstructure is formed by printing and forming, avoiding the crack problem that may occur during post-processing. This significantly increases the service life of the insulation equipment and improves the reliability of the equipment.
[0162] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for designing a vacuum alumina ceramic insulating component, characterized in that: The following steps are involved: S1: Optimizing the macrostructure to control the electric field distribution along the surface With the optimization goal of homogenizing the electric field along the surface of the ceramic insulating component and reducing the electric field intensity at the cathode triple junction, the finite element method is used to discretize the ceramic insulating component region to obtain multiple grids. The dielectric constant in each grid varies in the range from the substrate dielectric constant to the vacuum dielectric constant. Through the variable density topology optimization algorithm, and considering the mechanical performance requirements and the limitations of the algorithm parameter value range, the optimal spatial distribution of the dielectric constant inside the supporting ceramic insulating component is found, and then the macro structure is obtained; S2: Microstructure optimization and control of secondary electron multiplication Microstructures of different sizes are randomly generated on the surface of the macrostructure. Subsequently, particle simulation and Monte Carlo collision method are used to carry out surface discharge simulation research. The particle simulation method is used to track the motion state of particles, and the Monte Carlo collision method is used to deal with the collision process between particles. By reconstructing the secondary electron multiplication process, the surface structure size parameters of microstructures with low secondary electron yield are obtained, and then the mesostructure is obtained.
2. The design method of a vacuum alumina ceramic insulation component according to claim 1, characterized in that: In step S1, the design optimization variable is the relative dielectric constant in each grid after the dielectric constant optimization region Ω1 is discretized, which is expressed as follows: ε(r,z),(r,z)∈Ω1 Among them, r and z are the horizontal and vertical coordinates in the two-dimensional axisymmetric coordinate system, and the dielectric constant of each point after discretization is recorded as ε(r,z); After the optimization variables are determined, the mathematical expression of the optimization target f is obtained as follows: Among them, f1 is the electric field optimization term, f2 is the gradient penalty term, the weight coefficient q is used to control the proportion of the gradient penalty term in the total optimization target, Ω1 is the dielectric constant optimization area, Ω2 is the surface electric field optimization area; Ω3 is the local electric field optimization area at CTJ, C ref1 and C ref2 are the normalized parameters of the optimized components in the electric field integral term, A, h mesh and ρ are the area of the dielectric constant optimization region Ω1, the maximum size of the mesh, and the material density in the mesh, respectively. E is the electric field intensity in the surface electric field optimization region Ω2, and E mean is the average electric field strength along the surface.
3. The design method of a vacuum alumina ceramic insulation component according to claim 2, characterized in that: In step S1, the relationship between the material density ρ in the grid and the relative dielectric constant is as follows: Among them, ε ri , ε max and ε min are the dielectric constant, the upper limit of dielectric constant change and the lower limit of dielectric constant in the i-th grid, m is the shape control coefficient of density function, ρ i is the material density in the i-th grid.
4. The design method of a vacuum alumina ceramic insulation component according to claim 3, characterized in that: In step S1, when the finite element analysis is performed using the variable density topology optimization algorithm, the stress distribution of each grid under a given mechanical load is calculated at the same time. The relationship between stress and strain is expressed by Hooke's law: σ=M*ε Where σ is stress, M is the elastic modulus of the material, and ε is strain; The strain of each grid is calculated by finite element method to obtain the maximum stress S of the entire ceramic insulation component. max and the maximum deformation D max ; It is stipulated that the maximum deformation of ceramic insulation components under a given mechanical load shall not exceed the allowable value D f ,Right now: D max ≤D f That is, the constraints on the mechanical strength of the ceramic insulating component are obtained.
5. The design method of a vacuum alumina ceramic insulation component according to claim 4, characterized in that: In step S1, when performing finite element analysis using the variable density topology optimization algorithm, the following constraints are also included: 1≤m≤10.0<ρ i <1.0≤q≤10; The final optimization problem is: Design variables: ε(r,z),(r,z)∈Ω1 Optimization goal: Constraints: 0<m<10.0<ρ i <1.0≤q≤10 D max ≤D f Through multi-physics finite element simulation of electric field and solid mechanics field, the optimization parameters m, q and D are adjusted. max , and obtain the optimal spatial distribution of the dielectric constant inside the supporting ceramic insulating component.
6. The method for designing a vacuum alumina ceramic insulation component according to claim 5, characterized in that: After determining the optimization objectives and constraints, finite element simulation analysis software is used to establish the electric field and force field simulation model of the ceramic insulating component. The global moving asymptote optimization algorithm is used to solve the optimization problem, obtain the optimized material density distribution of the ceramic insulating component, and obtain the macro structure.
7. The method for designing a vacuum alumina ceramic insulation component according to claim 6, characterized in that: In step S2, the specific surface discharge simulation process is as follows: S21: Set the minimum forming size S of the microstructure min , dividing the macrostructure surface into N grid matrix units, using different types of lattice lattice structures, and determining the relationship between the minimum lattice lattice structure size parameters; S22: The obtained structures of different sizes are simulated by particle simulation and Monte Carlo collision method to simulate the electric field distribution and the motion trajectory of charged particles during the secondary electron multiplication process, and the optimized lattice structure size parameters are obtained to improve the vacuum surface electrical strength of the material.
8. The method for designing a vacuum alumina ceramic insulation component according to claim 7, characterized in that: In the step S21, the minimum lattice lattice structure size parameters include: the length l0 and width d0 of the lattice lattice, the height h0 of the lattice lattice, and the diameter z0 of the lattice lattice column. The relationship between the size parameters is as follows:
9. The method for designing a vacuum alumina ceramic insulation component according to claim 1, characterized in that: In step S22, the specific process of performing simulation by particle simulation and Monte Carlo collision method is as follows: S221: Particle Data Processing At a given incident angle θ and bombardment energy E i Under this condition, the total secondary electron emission coefficient δ is determined as follows: Among them, δ max is the maximum secondary electron emission coefficient corresponding to the secondary electron emission curve at vertical incidence, E max is the corresponding incident electron energy; k s is the roughness coefficient; E min is the minimum electron energy that triggers secondary electron emission; According to the above, the emission coefficients of the three types of electrons are obtained respectively, and the three types of electrons are: primary electrons scattered elastically; primary electrons scattered inelastically; true secondary electrons; S222: Electromagnetic Field Data Processing In the electrostatic model, the Poisson equation is solved by the explicit FDTD method to obtain the electrostatic potential, and the electrostatic field is obtained by solving the potential gradient equation. In the electromagnetic model, in order to circumvent the time step restriction of the CFL condition, the Maxwell equations are solved by the implicit FDTD method to obtain the RF electromagnetic field distribution, and the electrostatic field is solved in the same way as in the electrostatic model. S223: Particle data and grid data interaction The interaction between particles and grid data includes two processes: from particle data to grid data and from grid data to particle data. In the process of interaction from particle data to grid data, the charge density and current density on the grid are calculated based on the parameters such as the position and charge of the particle. In the process of interaction from grid data to particle data, the electromagnetic field of the grid is interpolated to the particle, thereby calculating the force on the particle. S224: Particle Collision Processing The Coulomb collision process between charged particles is treated by the Monte Carlo collision method.
10. A method for preparing an alumina ceramic insulating component for vacuum use, characterized in that: Based on the macroscopic structure and the microscopic structure obtained by the design method according to any one of claims 1 to 9, the ceramic insulating component is formed by using the light-curing ceramic 3D printing technology. The following steps are involved: S3: Stereolithography 3D Printing Alumina powder with a mass fraction of 70-85%, photocurable resin with a mass fraction of 5-14%, acrylate monomer with a mass fraction of 5-18%, UV photoinitiator with a mass fraction of 1-5%, and other additives with a mass fraction of 1-3% are dispersed and stirred using a vacuum planetary gravity mixer at a constant temperature of 40-50° C. The stirring speed is 1000-2000 rpm, and after stirring for 5-10 minutes, a mixed slurry with uniform dispersion and no bubble defects is obtained; the prepared mixed slurry is placed in a 3D printer material tank, and 3D printing is performed by a photocuring 3D printer to obtain an alumina ceramic component embryo; S4: Ceramic degreasing First, the temperature was raised from room temperature to 600°C at a heating rate of 1°C / min in a vacuum environment, and the temperature was kept at 200, 250 and 300°C for 90 minutes respectively, and at 600°C for 150 minutes; after the temperature dropped to room temperature, air was introduced into the tubular furnace, and the temperature was raised from room temperature to 600°C at a heating rate of 1°C / min, and then kept for 120 minutes and cooled with the furnace; S5: Ceramic sintering The sintering is completed in a high-temperature box furnace at 1750°C. During sintering, the temperature is first raised to 1400°C at a rate of 10°C / min, kept warm for 120 minutes, then raised to 1600°C at a rate of 5°C / min, and kept warm for 120 minutes; finally, the temperature is slowly raised to 1700°C at a rate of 2°C / min, and kept warm for 60 minutes to fully densify the ceramic body; finally, the temperature is naturally lowered to room temperature, and the sintered dense alumina component is taken out, that is, the alumina ceramic insulating component is obtained.
Citation Information
Patent Citations
Coaxial type high-current ceramic vacuum insulator based on surface non-uniform ripple
CN109243727A
Suppression method for partial discharge at flange of GIS / GIL supporting insulator
CN113470907A
A heater that uses dissolved and solidified salt as a heating medium
KR102428610B1
Method for preparing three-layer gradient GIS / GIL support insulator
WO2022267986A1
Preparation method for gradient insulating component
WO2023050531A1
Cited By
A Plasma Dynamics-Based Method for Predicting the Lower Surface Flashover Voltage of Perfluoroisobutyronitrile Mixed Gases
CN121980878B